Proprioception of foot and ankle complex in young regular practitioners of ice hockey, ballet dancing and running - Li, J. X.; Xu, D. Q.; Hoshizaki, B. (Research in Sports Medicine, 2010)
This study examined the proprioception of the foot and ankle complex in regular ice hockey practitioners, runners, and ballet dancers. A total of 45 young people with different exercise habits formed four groups: the ice hockey, ballet dancing, running, and sedentary groups. Kinesthesia of the foot and ankle complex was measured in plantarflexion (PF), dorsiflexion (DF), inversion (IV), and eversion (EV) at 0.4°/s using a custom-made device. The results showed the following: (1) significantly better perceived passive motion sense in PF/DF was found as compared with the measurements in IV/EV within each group (P < .01); (2) ice hockey and ballet groups perceived significantly better passive motion sense in IV/EV than the running (P < .05) and the sedentary (P < .01) groups; and (3) no significant difference in the all measurements was found between running and sedentary groups. The benefits of ice hockey and ballet dancing on proprioception may be associated with their movement characteristics.